Predict Observe Explain Learning Model : Implementation and Its Influence on Students’ Critical Thinking Ability and Learning Outcomes (A Meta-Analysis Study) - Rina Gustina; Intan Dwi Hastuti; Muhammad Nizaar; Syaharuddin Syaharuddin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to examine the application of the POE (Prediction, Observation, and Explanation) learning model in Mathematics and Natural Sciences learning in the last 10 years in terms of advantages and constraints in Mathematics and Natural Sciences learning at elementary school, junior high school, and senior high school levels. The research used meta-analysis with a quantitative approach and data collection of Scopus/WoS and SINTA journals literature studies on POE in MIPA learning combined with MIPA materials for elementary school, junior high school, and senior high school. The data collection techniques of this research were (1) searching journal and repository databases, (2) data encoding & tabulation, (3) JASP software inputs, (4) interpretation & conclusion: JASP output, moderator variables. The research results showed that applying the POE learning model had a greater effect on student Learning Outcome than on student Critical Thinking with an effect of 60%. Then based on the education level, the POE model's influence on Critical Thinking and Student Learning Outcome was greater at the senior high school level, and based on the material field, the POE model had a greater influence on the mathematics material field. Then the moderator variable showed a very drastic decrease in the effect of the POE model on the Critical Thinking and Learning Outcome of students in 2018-2022, with a RE value of 47% smaller than the previous year. In addition, we recommend that the POE model is better applied at the high school level than at the elementary and junior high school levels.